STRATEGI PENINGKATAN PEMBELAJARAN AKSESORIS RAMBUT DENGAN PEMANFAATAN KAIN PERCA DAN MANIK-MANIK - Yuwati, Herina; Warsihapsari, Tri (Jurnal Socia Akademika, 2024)
This study aims to determine how far students are interested in hair accessories courses. The research methods used are quantitative and qualitative descriptions. The subjects in this study are 33 people from the 3rd semester of the AKS AKK Yogyakarta Cosmetology Study Program. Data collection uses interview documentation and observation of interview methods, observation is intended to obtain detailed data on the manufacture of hair accessories. Documentation is used to describe the results of hair accessories practice that students have done using patchwork. From the results obtained in the study, 30 students stated that this learning could increase students' creative ideas in making hair accessories and 3 students indicated that they had not received the impact of increasing learning motivation